Constructing the Meaning of Women in Islamic Education: A Discourse Analysis of Kitab Kuning from a Philosophy of Science Perspective - Syifa Firahmatika; Dwi Puspa Krismayanti; Muhammad Fadloli; Sumadi Sumadi (Jurnal Ilmiah Mandala Education (JIME), 2026)
As a faith-based educational institution, the pesantren initially emerged as a center for the cultivation of religious values and the dissemination of Islam. Because its primary character is that of an Islamic educational institution, the pesantren has, over time, systematically developed a distinctive Islamic tradition. One enduring hallmark of this tradition is the continued practice of reading and teaching kitab kuning (classical Islamic texts). Sustained for generations, the study of kitab kuning has become a substantive and authoritative reference within pesantren communities. Moreover, the pesantren’s emphasis on the continuity of sanad, which traces chains of transmission back to the Prophet and earlier scholars, positions kitab kuning not merely as instructional materials but also as a medium for transmitting scholarly authority grounded in recognized lineages of knowledge. However, when classical texts are treated as normative references, their discourse may operate as an epistemic regime that legitimizes particular moral orders and shapes socio-religious identities within educational practice. This article examines how Shaykh Nawawi al-Bantani’s ‘Uq?d al-Lujayn f? Bay?n ?uq?q al-Zawjayn constructs meanings about women and how these meanings are reproduced as pedagogical “truths” in Islamic education in pesantren. Methodologically, this study employs a library research design by integrating: (1) Michel Foucault’s power/knowledge framework to explain regimes of truth and disciplinary normalization; (2) Norman Fairclough’s Critical Discourse Analysis to map textual strategies and their articulation with discursive and social practices; and (3) Paulo Freire’s critical pedagogy to formulate a dialogical reconstruction of learning. The primary data are drawn from the Indonesian translation, Syarh ‘Uq?d al-Lujayn (Etika Berumah Tangga), including its internal citations (Qur’anic verses, hadith reports, and moral narratives). Secondary data consist of recent scholarly studies on gender discourse in pesantren, kitab kuning scholarship, and reputable theoretical works in hermeneutics and philosophy of education. Findings based on the primary text indicate that ‘Uq?d al-Lujayn frames women predominantly within a relational and hierarchical ontology centered on husband and wife relations, elevates obedience and domestic piety as moral ideals, and strengthens its claims through the situated citation of scriptural evidences and appeals to scholarly authority. This argumentative structure generates asymmetric moral standards that may function as a hidden curriculum in pesantren learning. The article contributes to Islamic educational philosophy by offering an epistemological critique of classical-text authority and proposing a pedagogical reconstruction through critical and dialogical reading, contextual hermeneutics, and gender-just interpretive principles.